Clinical outcomes of intraoperative dopamine infusion for hypotensive patients during breast reconstruction with deep inferior epigastric perforator (DIEP) flaps. Issue 9 (September 2022) - Rhee, Daniel H.; Constantine, Ryan S.; Colakoglu, Salih; Karimpour-Fard, Anis; Kaoutzanis, Christodoulos; Mathes, David W.; Chong, Tae W.
Summary: Background: Dopamine has a favorable therapeutic profile but has not been widely used to treat hypotension during microvascular breast reconstruction. The purpose of this study was to evaluate outcomes in patients who received dopamine during breast reconstruction using deep inferior epigastric perforator (DIEP) free flaps and compare them with patients who did not receive dopamine. Methods: A single-center retrospective review was performed for patients who underwent breast reconstruction with DIEP free flaps between October 2018 and March 2020. Patient demographics, comorbidities, fluid balance, hospital stay, and adverse outcomes were compared between patients who received at least 1 h of dopamine (DA) and patients who did not receive dopamine (ND). Subgroup analyses were performed for bilateral procedures and patients who received dopamine. Results: Twenty-five patients in the DA group and 43 patients in the ND group met the inclusion criteria. There were no flap-related complications. Patients who had dopamine initiated to maintain blood pressures had a higher total volume of intravenous fluid (ND:3.81L vs. DA:5.04L, p = 0.005). However, DA patients exhibited decreased fluid requirements (ND:839 mL/h vs. DA:479 mL/h, p = 0.004) and increased urine output (ND:98.0 mL/h vs. DA:340 mL/h, p = <0.001) once dopamine was initiated. Intraoperative urine output (ND:1.37 L vs. DA:3.48 L, p < 0.001) and rate (ND:1.9 ml/kg/h vs. DA:3.7 ml/kg/h, p < 0.001) were increased in the DA group. The fluid balance of patients undergoing bilateral procedures was closer to neutral for patients who received dopamine (ND:+3.43 L vs. DA:+2.26 L, p = 0.03). Conclusion: Dopamine is safe to use in microvascular breast reconstruction. It may be beneficial for hemodynamically labile patients by stabilizing blood pressure and facilitating a neutral fluid balance. Graphical abstract: Image, graphical abstract